Assessment of Sexual Health Knowledge, Attitudes, Practices and Dysfunction in Women Attending Obstetrics and Gynaecology OPD - Bhumika Mishra; Sujatha MS; T S S Rao (Journal of Psychosexual Health)
Background: Despite the fact that there have been significant advances in the prevention and treatment of sexual dysfunction in India, the majority of these have focused on male sexual dysfunction disorders and there is still a paucity of literature that adequately explains the relationship between sexual knowledge and attitudes and female sexual dysfunction (FSD). Furthermore, physiological events such as pregnancy, childbirth, breastfeeding, menopause, and ageing have a significant impact on sexual well-being, particularly when co-morbid psychiatric illnesses are present. The prevalence of these interactions and their relationship with FSD is expected to have consequences in the prevention and treatment of FSD. Aim: To assess sexual health knowledge and attitudes regarding sexual practices in women attending Obstetrics and Gynaecology OPD and assess presence and extent of sexual dysfunction in them. Methods: This was a hospital-based cross-sectional study with a sample size of 220 women in the category of pregnant, nulliparous and perimenopause/menopause/post menopause. The SKAQ-II (Sexual Knowledge and Attitude questionnaire) assessed their sexual knowledge and attitude, and Female Sexual Functioning Index scale (FSFI) evaluated sexual dysfunction. Results: Ninety-three percent of the women had an adequate amount of knowledge regarding sexual practice and 83.2% had a liberal attitude. Rural women had lower levels of sexual knowledge and a conservative attitude towards sexual practice. Level Sexual knowledge and attitude were positively correlated with the presence of sexual dysfunction, with the prevalence of later being 65.5%—with 63% of pregnant women having sexual dysfunction, and 77.8% of menopausal women having sexual dysfunction. Conclusion: Women with greater sexual knowledge and a liberal mindset towards sexual practices tend to have lower levels of sexual dysfunction. Rural women tended to have lower levels of sexual knowledge and a poor attitude towards sexual practice, there was no association found between religious attitudes. Most dysfunction was faced by the menopausal age group. Sexual issues were more common in the domains of desire, lubrication, orgasm and pain. A positive correlation was noted between sexual dysfunction and kind of housing, leading to a lack of intimacy being an important contributing factor.